Immunotherapy Combined with Large Fractions of Radiotherapy: Stereotactic Radiosurgery for Brain Metastases—Implications for Intraoperative Radiotherapy after Resection - Herskind, Carsten; Wenz, Frederik; Giordano, Frank A. (Frontiers in Oncology, 2017)
Brain metastases (BM) affect approximately a third of all cancer patients with systemic disease. Treatment options include surgery, whole-brain radiotherapy, or stereotactic radiosurgery (SRS) while chemotherapy has only limited activity. In cases where patients undergo resection before irradiation, intraoperative radiotherapy (IORT) to the tumor bed may be an alternative modality, which would eliminate the repopulation of residual tumor cells between surgery and postoperative radiotherapy. Accumulating evidence has shown that high single doses of ionizing radiation can be highly efficient in eliciting a broad spectrum of local, regional, and systemic tumor-directed immune reactions. Furthermore, immune checkpoint blockade (ICB) has proven effective in treating antigenic BM and, thus, combining IORT with ICB might be a promising approach. However, it is not known if a low number of residual tumor cells in the tumor bed after resection is sufficient to act as an immunizing event opening the gate for ICB therapies in the brain. Because immunological data on tumor bed irradiation after resection are lacking, a rationale for combining IORT with ICB must be based on mechanistic insight from experimental models and clinical studies on unresected tumors. The purpose of the present review is to examine the mechanisms by which large radiation doses as applied in SRS and IORT enhance antitumor immune activity. Clinical studies on IORT for brain tumors, and on combined treatment of SRS and ICB for unresected BM, are used to assess the safety, efficacy, and immunogenicity of IORT plus ICB and to suggest an optimal treatment sequence.